The Relationship Between Leadership's Interpersonal Communication and Team Performance at Love Strings Event Organizer Surabaya - Johan Wijaya TJENDRA; Hilda Yunita WONO (PT Keberlanjutan Strategis Indonesia, 2025)
His study aims to analyze the impact of leadership's interpersonal communication on employee performance at Love Strings Event Organizer Surabaya. The research, conducted using a quantitative descriptive approach, involved 50 respondents from both full-time and freelance employees, with data collected through a Google Form questionnaire. The analysis revealed a positive and significant influence of leadership's interpersonal communication on employee performance. The simple linear regression analysis showed a regression coefficient of 0.873 with a significance level of 0.009, indicating that the better the communication between leadership and employees, the higher the performance achieved. The R² value of 0.860 indicates that 86% of the variation in employee performance can be attributed to the quality of leadership's interpersonal communication. In the dynamic and fast-paced event organizer industry, clear, open, and targeted communication proved to foster effective teamwork, enhance coordination, and increase individual and group responsibility. This study emphasizes the significance of effective communication in leadership development and team management, particularly in project-based settings.